Attachment and sexual functioning in women and men seeking fertility treatment. (3rd July 2019) - Purcell-Lévesque, Coralie; Brassard, Audrey; Carranza-Mamane, Belina; Péloquin, Katherine
Abstract: Objective: The purpose of the study was to examine the frequency of sexual difficulties and the associations among attachment insecurities (anxiety, avoidance) and sexual functioning (problems with sexual function, sexual dissatisfaction) in women and couples seeking fertility treatment. Methods: In a cross-sectional study, 88 Canadian women and 45 couples receiving fertility treatments completed self-reported measures of adult attachment and sexual functioning. Results: The frequency of problems in sexual function varied from 14.8% (pain) to 58.0% (desire) in women and from 6.7% (satisfaction with orgasm) to 28.9% (desire) in men. Among women, attachment-related avoidance predicted their low levels of sexual satisfaction ( β  = −0.30, p =  .007) and sexual pain ( β  = 0.22, p  = .044). Dyadic analyses revealed associations between men's attachment-related anxiety and their difficulties in reaching erection ( β  = 0.30, p  = .042) and orgasm ( β  = 0.33, p  = .009). Anxiety in women was related to their lubrication difficulties ( β  = 0.44, p  = .006). One partner effect was found: men's avoidance was related to their partners' difficulty in achieving orgasms ( β  = 0.39, p  = .045). Conclusions: Results support the pertinence of attachment theory and the relevance of using dyadic designs to understand sexuality in couples seeking fertility treatment.